1D CdS nanowire–2D BiVO4 nanosheet heterostructures toward photocatalytic selective fine-chemical synthesis1. Issue 21 (6th March 2015) - Han, Bin; Liu, Siqi; Xu, Yi-Jun; Tang, Zi-Rong
<x xml:space="preserve">Abstract</x> The CdS–BiVO4 1D/2D composite is fabricated by a simple electrostatic self-assembly methodology, which exhibits a significantly enhanced photocatalytic performance as compared to bare 1D CdS and 2D BiVO4.